The prospective of particle image velocimetry (PIV) measurement velocity profile in thermoacoustic system - Siti Norsyahira, Mohd Zahari; Nor Atiqah, Zolpakar; Mimi Muzlina, Mukri (ISRES Publishing, 2022)
Precise measurement of fluid velocities is essential in several applications, including thermoacoustic refrigeration systems. A thermoacoustic refrigeration system uses a high-amplitude acoustic standing wave to generate a cooling effect. Understanding the fluid flow characteristic between the refrigerant and a stack is important to improve the heat transfer process and minimise thermal and viscous losses. This paper reviews the various methods employed by previous researchers in analysing the velocity profiles in the thermoacoustic refrigeration system and the prospective implementation of Particle Image Velocimetry (PIV). PIV is a non-invasive technique that estimates velocity at several points of the measuring region. This review looked at the method employed to analyse the velocity profile, error analysis, and the effectiveness of another measurement method compared to the PIV measurement. The discussions include related parameters that past researchers have considered.